(untitled) (Research, Society and Development, 2022)
With the growth of the forest sector, the foresters are becoming more exigent in terms of productivity and forest management. The eucalypt plantations are very important, helping in the reduction of deforestation native forests. In this context, geostatistic represents a tool that has been used in the forest sciences to perform good estimations with a small number of data collections. Thus, the present study aimed to evaluate the spatial variability of the dendrometric properties of Eucalyptus urophylla cultivated in the Cerrado Biome. The dataset used in this study is derived from the clonal stand eucalypt of Federal University of Tocantins. In 40 distributed geodesic points in a regular sampling grid four variables were collected: vertical length, longitudinal length, stem diameter at 10 cm and stem diameter at 50 cm. With the help of GS+® and Surfer®, the spatial variability maps were created for each attribute. The kriging was defined as the interpolation method in this step. According to the results, all analyzed variables showed a high degree of spatial dependence. The spherical model was the spherical model was the best adjusted. The range with similar value for all attributes showed homogeneity on the E. urophylla stand. Thus, it is concluded that the maps made based on geostatistical analyzes presented relevant results.